Diseño de un manual de buenas prácticas de manufactura en el taller de procesos de harinas y balanceados ESPAM-MFL - Avellán Chancay, Lidice Jeniffer (2013)
This project deals with the design of a manual for good manufacturing practices in the workshop process and balanced meal of ESPAM - MFL, this manual was designed specifically for quality improvement in processes, raw material supply and better quality safe products. In the balanced meals workshops products such as balanced meal for cattle and pigs at all stages of growth are elaborated, the workshop needs to develop a manual for implementing GMP in all activities undertaken. The aim of this study was to conduct a diagnosis while designing a manual Good Manufacturing Practices in the workshop. For the execution of this research was conducted initial diagnosis using observation sheet to identify the current state of the plant, then conducted an interview to shop technician to know their knowledge on GMP and its importance, then know about their products and processes. As next step was to apply SWOT analysis (strengths, weaknesses, opportunities, threats), EFE (External factors evaluation), IFE (internal factors evaluation), which sought to design and implement strategies that help plant improvement. It was concluded that the company has many opportunities for improvement in terms of GMP and need to apply the guidelines set out in the manual of GMP development.